Teaching Module Design in Expanding Student Character in the Independent Curriculum at SMAN 3 Jayapura - Ananda Yusdiva; Naufal Ahmad Rijalul Alam (At-Tarbiyat, 2024)
Education helps students make the best possible adjustment to their surroundings and can produce changes in themselves that allow them to operate in communal life. Character education is essential for guiding people towards excellent ethics or morals. The Independent Curriculum (Kurikulum Merdeka) is part of the government's efforts to address the long-standing learning crisis, which is exacerbated by the epidemic, by imparting student character education in accordance with the Pancasila student profile. Students will develop positive character traits as a result of the design of appropriate educational modules. Because this research will discuss the design of instructional modules, it will be conducted qualitatively. The findings suggest that the ideal teaching module design incorporates criteria and components from the Pancasila (P5) student profile.